Global perspectives on unmanned aerial vehicles technology in social sciences: Applications, innovations, and future research directions - Ricky Anak Kemarau; Zaini Sakawi; Stanley Anak Suab; Oliver Valentine Eboy; Wan Shafrina Wan Mohd Jaafar; Khairul Nizam Abdul Maulud; Nik Norliati Fitri Md Nor (Taylor & Francis, 2024)
Unmanned aerial vehicles (UAVs), or drones, are transforming social science research by introducing innovative methodologies for data collection and analysis. This study systematically reviews the last two decades of literature to evaluate the role of UAVs across various social science disciplines, including archaeology, geography, public health, and disaster management. The analysis reveals that UAVs significantly enhance research capabilities by improving data accuracy, resolution, and accessibility, particularly in remote or challenging environments. Despite these advancements, challenges such as privacy concerns, ethical considerations, and technical limitations persist. The study underscores the need for interdisciplinary collaboration and the development of ethical frameworks to guide UAV integration in social sciences. The findings advocate for the continued exploration of UAV technology to address existing challenges and expand its applications, paving the way for future research that can further enhance the impact of UAVs on social science methodologies.